2022
DOI: 10.5851/kosfa.2022.e28
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Nondestructive Prediction of Multiple Quality Attributes for Different Commercial Meat Cut Types Using Optical System

Abstract: There are differences of spectral characteristics between different types of meat cut, which means the model established using only one type of meat cut for meat quality prediction is not suitable for other meat cut types. A novel portable visible and near-infrared (Vis/NIR) optical system was used to simultaneously predict multiple quality indicators for different commercial meat cut types (silverside, back strap, oyster, fillet, thick flank, and tenderloin) from Small-tailed Han sheep. The correlation coeffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…However, as this study was a review of previous research within a relatively limited field, concluding that its results represent global research trends in the field of animal agriculture and food may be difficult; hence, continuous monitoring through additional follow-up studies is warranted. [110], [111], [112], [113], [114], [115], [116] Malt Genomic DNA; inflammation; Pediococcus acidilactici; periodontitis; Porphyromonas gingivalis [106] Meat Gut microbiota; meat; protein digestion; proteolytic enzyme; sous-vide [117] Meat products Authentication; essential oils; lipidomics; liquid chromatography-mass spectrometry; low-salt meat products; low-sodium meat products; meat product; metabolomics; nanoemulsion; natural preservative; natural salt replacers; salt alternatives; salt-modifying; salt reduction [118], [119], [120] Meat water-holding capacity; whey; whey protein; whipping cream; whipping property; yogurt [122], [123], [124], [125], [126], [127], [128], [129], [130], [131], [132], [133],…”
Section: Discussionmentioning
confidence: 99%
“…However, as this study was a review of previous research within a relatively limited field, concluding that its results represent global research trends in the field of animal agriculture and food may be difficult; hence, continuous monitoring through additional follow-up studies is warranted. [110], [111], [112], [113], [114], [115], [116] Malt Genomic DNA; inflammation; Pediococcus acidilactici; periodontitis; Porphyromonas gingivalis [106] Meat Gut microbiota; meat; protein digestion; proteolytic enzyme; sous-vide [117] Meat products Authentication; essential oils; lipidomics; liquid chromatography-mass spectrometry; low-salt meat products; low-sodium meat products; meat product; metabolomics; nanoemulsion; natural preservative; natural salt replacers; salt alternatives; salt-modifying; salt reduction [118], [119], [120] Meat water-holding capacity; whey; whey protein; whipping cream; whipping property; yogurt [122], [123], [124], [125], [126], [127], [128], [129], [130], [131], [132], [133],…”
Section: Discussionmentioning
confidence: 99%
“…Prediction of meat quality in fresh cut was reported by ( An et al, 2022 ), while after treatment in the abattoir was reported by ( Savoia et al, 2020 ; Savoia et al, 2021 ). Li et al proposed a rapid and nondestructive simultaneous characterization of different types of sheep meat cut ( Li et al, 2021 ).…”
Section: Applications To Food Quality Characterization and Adulterationsmentioning
confidence: 99%
“…Therefore, the selection of raw meat with high myofibrillar protein solubility is extremely important to manufacture low-salt meat products. Various techniques have been developed to predict meat quality [ 55 , 56 ]. The selection of raw meat with proven quality using prediction techniques can effectively improve the quality of low-salt meat products.…”
Section: Reduction Of the Ingredients Potentially Harmful When Overco...mentioning
confidence: 99%